Case report: A novel HNF1A variant linked to gestational diabetes, congenital hyperinsulinism, and diazoxide hypersensitivity - Chandran, Suresh; Verma, Deepti; Rajadurai, Victor Samuel; Yap, Fabian (Frontiers in Endocrinology, 2024)
Diazoxide (DZX) remains the first-line medication for the treatment of prolonged and persistent forms of hyperinsulinemic hypoglycemia (HH). In nearly 40-50% of cases of HH, the genetic mechanism is unidentified. Almost half of the infants with permanent or genetic causes are DZX sensitive, but hypersensitivity to DZX is extremely rare, and the mechanism is poorly understood. Here, we report for the first time a case of DZX hypersensitivity in a neonate with HH who inherited a novel HNF1A variant from the mother. A term male largefor-gestational-age infant of a diabetic mother presented with early onset of severe, recurrent hypoglycemia. Critical blood samples when hypoglycemic confirmed HH. Diazoxide was initiated at conventional doses of 5 mg/kg/day, which resulted in hyperglycemia (blood glucose, 16.6 mmol/L) within 48 hours. Glucose infusion was rapidly weaned off. DZX was withheld and eventually stopped. Following 3 days of milk feeds alone with a normal glucose profile, suspecting a resolution of HH, he underwent a 6-hour fasting study and passed. While on glucose monitoring in the hospital, he again developed hypoglycemic episodes, and the critical blood samples confirmed HH. DZX was restarted at a lower dose of 3 mg/kg/day, which required further down-titration to 0.7 mg/kg/day before steady euglycemia was obtained. No more episodes of hypo or hyperglycemia occurred, and he passed a safety fasting study before discharge. Molecular genetic testing identified a novel HNF1A mutation in the mother-child dyad, whereas the father tested negative. We concluded that the HH phenotype due to this novel HNF1A mutation can be mutation-specific and require a very low dose of DZX. Clinicians should observe closely for the risk of diabetic ketoacidosis and hyperglycemic hyperosmolar state while initiating DZX therapy.